Possible effects of an early diagnosis and treatment in patients with growth hormone deficiency: the state of art - Stefano Stagi; Perla Scalini; Giovanni Farello; Alberto Verrotti (BMC, 2017)
Abstract Growth hormone deficiency (GHD) is a relatively uncommon and heterogeneous endocrine disorder presenting in childhood with short stature. However, during the neonatal period, the metabolic effects of GHD may to require prompt replacement therapy to avoid possible life-threatening complications. An increasing amount of data suggests the importance of an early diagnosis and treatment of GHD because of its auxological, metabolic, and neurodevelopmental features with respect to the patients diagnosed and treated later in life. The available results show favourable auxological outcomes for patients with GHD diagnosed and treated with r-hGH early in life compared with those from patients with GHD who do not receive this early diagnosis and treatment. Because delayed referral for GHD diagnosis and treatment is still frequent, these results highlight the need for more attention in the diagnosis and treatment of GHD. Despite these very encouraging data regarding metabolic and neurodevelopmental features, further studies are needed to better characterize these findings. Overall, the importance of early diagnosis and treatment of GHD needs to be addressed.